The Latitudinal Distribution of Morphological Diversity among Holocene Angiosperm Pollen Grains from Eastern North America and the Neotropics. (2nd August 2018) - Mander, Luke
Abstract: Current knowledge about the biogeographic patterns of biodiversity is based mostly on taxonomic diversity, which is typically measured as the number of species or higher taxa. In this paper I analyze 26 previously published Holocene lake core pollen records in order to assess how the morphological diversity of angiosperm pollen grains varies with latitude on a transect that includes eastern North America and the Neotropics. This represents a step toward understanding the evolution of plant morphology in a biogeographical context. I employ a system of eight discrete characters to describe first-order features of angiosperm pollen morphology and use algorithms written in the Python programming language to assess their morphological diversity. There is no statistically significant relationship between taxonomic diversity and morphological diversity in the samples of Holocene angiosperm pollen investigated here. The number of pollen morphotypes in the sediment samples investigated here increases from high latitudes to the tropics, but the highest morphological diversity occurs at high latitudes, and the lowest morphological diversity occurs at mid-latitudes around 40–50° N. At the biome level, there are peaks in morphological diversity at low and high latitudes with a trough in mid latitudes. There is evidence of high levels of pollen morphotype endemism in the tropical biome, and further work on how the volume of morphological space varies with latitude is needed in order to understand whether taxa in species-rich tropical ecosystems are more densely packed into morphological space.